Beautiful little fools : a novel - Cantor, Jillian (Harper, an imprint of HarperCollins Publishers, 2022)
When Jay Gatsby is shot dead in his West Egg swimming pool, it appears to be an open-and-shut case of murder/suicide when the body of George Wilson is found in the woods nearby. Then a diamond hairpin is found in the bushes by the pool, and three women fall under suspicion. Each holds a key that can unlock the truth to the mysterious life and death of the millionaire. Daisy Buchanan once thought she might marry Gatsby, before her family was torn apart by a tragedy that sent her into the arms of Tom Buchanan. Jordan Baker, Daisy's best friend, guards a secret that threatens to ruin her friendship with Daisy. Catherine McCoy fights for women's freedom, especially for her sister, Myrtle Wilson, who is trapped in a terrible marriage. Their stories unfold in the years leading up to that fateful summer of 1922, when all three of their lives are on the brink of unraveling. Each woman is pulled deeper into Jay Gatsby's romantic obsession, with devastating consequences for all of them.